2015
DOI: 10.1128/jcm.00502-15
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Pan-Azole-Resistant Aspergillosis

Abstract: High-level pan-azole-resistant Aspergillus fumigatus was recovered from four patients with chronic lung disease. In one patient, the development of progressive resistance followed long-term azole therapy and switching between antifungal azoles. The highlevel pan-azole-resistant phenotypes were not associated with a specific cyp51A gene mutation. New strategies that avoid the development of progressive azole resistance are needed.A zole resistance in Aspergillus fumigatus is an emerging problem which is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The same group pioneered resistance surveillance of environmental isolates and reported major TR/L98H mutations in 44/630 ARAF isolates (42); they also reported the first TR46/Y121F/T289A mutations in 6/1,210 resistant environmental isolates (50). TR/L98H is the most common cyp51A mutation and has been previously reported in this patient population from various parts of the world, namely, Nijmegen, Netherlands (Europe) (7,9,12,13); Germany (Europe) (11); Poland (Europe) (51), the United States (North America) (52); Taiwan (53); Australia (54); the Middle East (34,55); and New Delhi, India (15). However, this mutation has been linked with the environmental spread of resistance due to the increasing use of fungicidal azoles in agricultural practices in Copenhagen, Denmark (Europe) (56); Bogotá, Colombia (Latin America) (57); Kuwait (Middle East) (34); and New Delhi, India (36).…”
mentioning
confidence: 69%
“…The same group pioneered resistance surveillance of environmental isolates and reported major TR/L98H mutations in 44/630 ARAF isolates (42); they also reported the first TR46/Y121F/T289A mutations in 6/1,210 resistant environmental isolates (50). TR/L98H is the most common cyp51A mutation and has been previously reported in this patient population from various parts of the world, namely, Nijmegen, Netherlands (Europe) (7,9,12,13); Germany (Europe) (11); Poland (Europe) (51), the United States (North America) (52); Taiwan (53); Australia (54); the Middle East (34,55); and New Delhi, India (15). However, this mutation has been linked with the environmental spread of resistance due to the increasing use of fungicidal azoles in agricultural practices in Copenhagen, Denmark (Europe) (56); Bogotá, Colombia (Latin America) (57); Kuwait (Middle East) (34); and New Delhi, India (36).…”
mentioning
confidence: 69%
“…Even though acquired resistance during therapy is rare, epidemiological studies have shown that Aspergillus azole resistance has increased over the past decade in patients with prolonged exposure to azoles, notably those with CPA ( 3 ). Mutations in the cyp51A gene leading to amino acid substitutions in the target enzyme lanosterol 14α-demethylase are the major mechanism of azole resistance ( 1 , 4 , 5 ), yet non- cyp51A -mediated resistance has been recently reported ( 6 ).…”
Section: Textmentioning
confidence: 99%
“…The mechanisms driving the development of azole resistance in A. fumigatus are not well understood. It is unclear whether clinically significant azole resistance is acquired de novo within the host due to the selection pressure of prolonged azole therapy, or through host inhalation of an azole resistant environmental isolate, resistance developed in the context of prolonged exposure to agricultural azole based fungicides [ 95 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ].…”
Section: Treatments Barriersmentioning
confidence: 99%